ANALISIS POTENSI GREEN WAQF DALAM MENDUKUNG TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGs) - Ikrimatu Khoirinnisa’; Fitri Intan Nuraini; Bayu Perdana; Amalia Nuril Hidayati (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Sustainable development (the Sustainable Development Goals, or SDGs) is an international agenda aimed at achieving a balance between economic growth, social well-being, and environmental conservation. To achieve these goals, financing instruments are needed that can provide long-term benefits while supporting environmental sustainability. One instrument with significant potential is the green waqf the management of waqf assets and funds directed toward environmentally friendly activities such as forest conservation, reforestation, renewable energy development, clean water management, and sustainable agriculture. This study aims to analyze the potential of green waqf in supporting the achievement of the Sustainable Development Goals (SDGs) and to identify the various challenges faced in its implementation in Indonesia. The method used in this study is qualitative, employing a literature review approach. Data were obtained from various sources, including scientific journals, books, articles, and relevant previous studies, which were then analyzed using a descriptive-analytical method. The findings indicate that green waqf holds strategic potential as a philanthropic instrument in Islam capable of supporting the achievement of the Sustainable Development Goals (SDGs), particularly regarding poverty alleviation, the provision of affordable and clean energy, access to clean water and sanitation, efforts to mitigate climate change, and the conservation of terrestrial ecosystems. In addition to benefiting the environment, green waqf also contributes to community economic empowerment through the development of productive businesses, sustainable agriculture, and job creation. However, the implementation of green waqf still faces a number of challenges, including low public awareness, limited capacity of waqf managers, weak regulations, limited use of digital technology, and a lack of funding. Therefore, strengthening is needed in governance, regulations, inter-institutional collaboration, and human resource capacity building so that the potential of green waqf can be maximized in supporting sustainable development in Indonesia.